Monitoring deep Mediterranean rhodolith beds. Issue 3 (21st December 2015) - Basso, Daniela; Babbini, Lorenza; Kaleb, Sara; Bracchi, Valentina A.; Falace, Annalisa
Abstract: The protocols available for sampling and monitoring shallow subtidal rhodolith beds (RBs) are inadequate for the deep Mediterranean analogues, and need calibration in order to attain comparable results. After reviewing the present knowledge of the specificities of Mediterranean RBs, and in the framework of the ongoing international effort for their conservation, a two‐step approach is suggested for their definition, identification, delimitation, description, and monitoring. Regional mapping should be improved, and RBs should be identified and delimited as those areas of the sea floor with >10% cover of live rhodoliths over a minimum surface of 500 m 2, on 1:10000 scale. More detailed scales (at least 1:1000) should be used for monitoring selected RBs, in order to detect significant changes through time. Beside location and areal extent, the description of RBs should include the occurrence of macroscopic sedimentary structures of the sea floor, thickness of live cover, mean percentage cover of live thalli and surface live/dead ratio, cover of dominant morphologies of rhodoliths (simplified on a ternary diagram), and volumetrically important calcareous algal species. For the purpose of assessment of the ecological status and the evaluation of human‐induced impacts, quantitative data about community composition are required. The comparative assessment of ecological status and the identification of RBs of high conservation value for special protection should consider the natural geographic and seasonal/annual variability of RBs. Copyright © 2015 John Wiley & Sons, Ltd.